2022
DOI: 10.1136/bmj-2022-069989
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of heterologous and homologous covid-19 vaccine regimens: living systematic review with network meta-analysis

Abstract: Objective To evaluate the effectiveness of heterologous and homologous covid-19 vaccine regimens with and without boosting in preventing covid-19 related infection, hospital admission, and death. Design Living systematic review and network meta-analysis. Data sources World Health Organization covid-19 databases, including 38 sources of published studies and preprints. Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 96 publications
(384 reference statements)
7
68
0
Order By: Relevance
“…Further, that a three-dose regimen is similarly effective in all age groups, even in people over 65. 15 Finally, in our study seven participants were infected with the Omicron variant (B.1.1.529), 2-5 months after the third dose. Owing to the large number of mutations in the spike protein, 16 there is concern that this variant will exhibit substantial escape from vaccineelicited immunity.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Further, that a three-dose regimen is similarly effective in all age groups, even in people over 65. 15 Finally, in our study seven participants were infected with the Omicron variant (B.1.1.529), 2-5 months after the third dose. Owing to the large number of mutations in the spike protein, 16 there is concern that this variant will exhibit substantial escape from vaccineelicited immunity.…”
Section: Discussionmentioning
confidence: 82%
“…In accordance with our study are the results of a recently published very interesting network meta‐analysis which found that the effect of two‐dose mRNA vaccines is weaker in those who are immunocompromised than in those who are non‐immunocompromised but a three‐dose mRNA regimen works comparably well in the non‐immunocompromised and immunocompromised individuals. Further, that a three‐dose regimen is similarly effective in all age groups, even in people over 65 15 …”
Section: Discussionmentioning
confidence: 99%
“…All one- and two-dose regimens failed in effectiveness against Delta and Omicron variants. A booster third dose is required to achieve the vaccine effectiveness agains new variants of concern [ 127 ].…”
Section: Immune Response To Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…Although some studies on COVID-19 booster vaccinations have been carried out, there is still a lack of a systematic description of homologous and heterologous booster vaccination against the SARS-CoV-2 variants. Besides, many studies only estimated the vaccine effectiveness rather than immunogenicity, so they cannot accurately represent the vaccine’s efficacy against a particular SARS-CoV-2 variant [ 12 , 13 ]. Therefore, our study will be the first summarizing the clinical trials of COVID-19 vaccine booster shots to compare the neutralization activity against the wild type and variants (Beta, Delta, and Omicron) in different prime–boost vaccination regimens, providing a useful reference for the recommendation of booster vaccinations.…”
Section: Introductionmentioning
confidence: 99%